2015
DOI: 10.1016/j.eurpolymj.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the design of co-poly(ether-imide) membranes for CO2 separations. Influence of aromatic rigidity on crystallinity, phase segregation and gas transport

Abstract: SummaryIn our previous works, it was observed a clear relationship between the structure and the properties for different copoly(ether-imide)s, besides a good relation was found between SAXS characterization and permeability results. Here, a series of aliphatic aromatic copoly(ether-imide)s, based on an aromatic diamine (ODA), a diamine terminated poly(ethylene oxide) (PEO2000) of a molecular weight of 2000 g/mol and different aromatic dianhydrides (BPDA, BKDA (or BTDA) and PMDA )has been synthesized and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…PEG-based polymeric membranes present potentials for CO 2 separation as they have high affinity towards CO 2 due to the ether segments. [30][31][32][33][34][35][36][37][38][39][40] However, they suffer from high crystallinity and weak mechanical strength. [41] PTMEG is a commercially available starting material derived from renewable resources that is more hydrophobic than PEG.…”
Section: Introductionmentioning
confidence: 99%
“…PEG-based polymeric membranes present potentials for CO 2 separation as they have high affinity towards CO 2 due to the ether segments. [30][31][32][33][34][35][36][37][38][39][40] However, they suffer from high crystallinity and weak mechanical strength. [41] PTMEG is a commercially available starting material derived from renewable resources that is more hydrophobic than PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Among glassy polymers, aromatic polyimides (PIs) are appealing materials in the view of fabricating gas separation membranes, due to their excellent gas permeability and good selectivity, and their good physico-chemical properties [11 , 58-62] . For example, PEO/polyimide has a high permeability and a high selectivity for CO 2 separation [63][64][65] . Copolyimides containing ethylene oxide have a higher diffusivity for CO 2 and N 2 than pure polyimides.…”
Section: Poly(ether-imide) Copolymer Membranesmentioning
confidence: 99%
“…The combination of PEO chains with poly(propylene oxide), poly(dimethyl siloxane),or other alkyl groups have proved to reduce crystallinity and increase permeability in the polymers. When PEO is copolymerized with other monomers that react to form rigid segments (aromatic polyimide segments, for example), a high selectivity is obtained, almost regardless of the composition of the rigid segments . With respect to the permeability, several parameters have been studied, and it was found that the main parameters were the content and the chain length of the PEO segments in the polymer .…”
Section: Introductionmentioning
confidence: 99%